Perceptions and Experiences of Nursing Students in Boromarajonani College of Nursing Changwat Nonthaburi regarding Active Learning - ระดาบุตร, เมทณี; ธานีรัตน์, สุภลักษณ์; ภิญโญมิตร, สุนทรี (Journal of The Royal Thai Army Nurses, 2019)
This research was phenomenologically designed. The objective was to study nursing students’ perceptions and experiences regarding active learning. Semi-structured interviews were conducted with 15 first-year nursing students studying in Boromarajonani College of Nursing, Changwat Nonthaburi, Academic Year 2018. Purposive sampling was used to select the participants. Data were analyzed following principles of Giorgi’s phenomenological method. The results of the study found that four core themes related to active learning emerged. There were: 1. active learning’ experience including 4 subthemes addressed passion of learning; teamwork; critical thinking; and participation between students and instructors, 2. Perceptions toward active learning method consisting of 3 subthemes addressed game-based learning; debated; and project-based learning, 3. benefits of active learning containing 4 subthemes included developing of critical thinking; increasing self-confidence; acknowledge of teamwork ;and inspiring of leaning, 4. barriers of active learning including 2 subthemes consisted of imbalance of workpiece with time; and instructors problems. The results of the research suggested that the nursing college promote active learning in several courses where learning activities were applied based on the agreement of the number of such activities and their corresponding required periods of time.